Selective Therapeutic Evaluation Using a Peroxide-Generating In-Vitro Three Dimensional Mod (Indo-American Journal of Life Sciences and Biotechnology, 2016)
The mouth is a promising medication delivery location because drugs taken orally bypass thedigestive system and first-pass metabolism, where they might be degraded. Delivery of medications via thebuccal mucosa to produce systemic pharmacological effects is what is meant by the term "buccal drugdelivery."Advantages of buccalbioadhesive films over conventional dosage forms may be seen in the treatment ofnumerous disorders due to the controlled and gradual release of topical medications in the mouth cavity.Thebuccal patch is a non-dissolving, thin-matrix, modified-release dosage form designed for the supine anduncooperative patient.[1] The buccal mucosa's accessibility, smooth, and inflexibility make it an ideal locationfor a bioadhesion system. Consequently, medications having a limited half life in the body. Oral flexible patcheshave been created to address the problems associated with taking pills. The purpose of this review is to educatereaders about buccal patches and the buccal medication delivery mechanism. Review the criteria used to assessbuccal patches.